Predictors of Patient Retention at a Student-Run Free Clinic - Matthew C Hess; Sebastian K Chung; James H Banos; Richard H Cockrum; Nicholas Van Wagoner; Craig Hoesley (Journal of Student-Run Clinics, 2018)
Background: Studies of patient retention at student-run free clinics (SRFCs) are lacking. We determined variables associated with clinic retention at Equal Access Birmingham (EAB), an urban SRFC that aims to provide acute care for clients with transitory health needs and longitudinal care for patients with chronic diseases. Methods: We retrospectively analyzed EAB patient data from March 1, 2013 to July 1, 2015, including demographic, social, medical history, and clinical care variables. The primary outcome was retention in care, defined as attendance at a follow-up appointment 6 to 12 months after the initial new patient visit. Potential predictors of retention were examined using stepwise multivariate logistic regression.Results: Patient retention rate was 25.2%. Positive predictors of retention included receipt of medication at the initial visit (odds ratio [OR] 15.40, 95% confidence interval [CI] 1.56-152.82), more kept appointments within 6 months of initial visit (OR 2.00, 95% CI 1.51-2.66), and longer time to follow-up (OR 1.14, 95% CI 1.04-1.26). Negative predictors included receiving only acute care at initial visit (OR 0.10, 95% CI 0.01-0.95), any appointment no-shows (OR 0.33, 95% CI 0.13-0.86), and cancellations (OR 0.29, 95% CI 0.09-0.87) within 6 months of an initial visit.Conclusion: This study is one of the first to analyze predictors of patient retention at a SRFC. Although we analyze a relatively small sample size in a single SRFC, our results inform strategies to better retain SRFC patients who have high rates of chronic illness and are vulnerable to loss to follow-up.